(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In this evolving modern world, technology is involved in all fields of human life. Mobile payment has become essential not only for consumer convenience but also for retailers’ business growth. Several studies have been undertaken to highlight the aspects that contribute to the establishment of “Behavioural Intention” among consumers for adopting mobile payments. Still, no studies are available in the context of India, as per the review of literature, which demonstrate the factors responsible for “Behavioural Intention” of retailers to adopt and use mobile payment in their day-to-day business. This study makes use of a “Five-point Likert Scale” to collect data from Indian retailers and establish a relationship between the selected variables for the study to fill the existing research gap present in the context of Indian retailers. Apart from UTAUT, “Performance Expectancy,” “Effort Expectancy,” “Social Influence,” “Facilitating Conditions,” and “Behavioural Intention,” “Perceived Security” is considered as one variable as there is always a security risk involved in using any digital technology. It is found that only “Effort Expectancy” and “Perceived Security” have a significant relationship with the Behavioural Intention of a retailer to use mobile payment. At the same time, “Performance Expectancy,”